Adaptasi Komunikasi Mahasiswa Tuli di Perguruan Tinggi - Marshya Camillia Ariej; Turnomo Rahardjo (Interaksi Online, 2020)
The communication problem faced by Deaf college students in campus is the difference ability of their communication skills with the hearing students. This difference in ability, led them to some communication barriers. The difference in understanding between Deaf students and their hearing environment arises because there are no mutual understanding between participants in communication caused by verbal symbols that are not captured in their entirety. The verbal symbols that matters are languages. Efforts and processes to achieve mutual understanding between Deaf people and other participants in communication are hampered due to these physical limitations. Deaf people are more dominant using non-verbal symbols (Sign Language) compared to verbal symbols. This study aims to understand the experiences and communication barriers of Deaf students when adapting to the hearing environment in higher education through a phenomenological approach. This study uses the foundation of Communication Accommodation Theory by Howard Giles and Social Learning Theory by Albert Bandura. This study uses in-depth interviews as data collection techniques involving four Deaf students with severe Deaf categories. The results of this study indicate, Deaf students not only face obstacles in verbal but also language communication in the verbal form. Deaf students accept prejudice and discrimination from the environment expressed through refusal and demands to always use verbal symbols when interacting and communicating. In addition, Deaf students also experience anxiety, uncertainty, and foreign language barriers (English) in academic terms. Apprehension that occurs in Deaf students is a Situational Communication Apprehention. Besides experiencing communication apprehension, Deaf students are also faced with uncertain situations when they first become students. Three uncertainty reduction strategies namely passive, active and interactional are used by Deaf students when facing certain situations that cause uncertainty. A new theory emerged and it could explain the phenomenon of adaptation of deaf students in higher education, namely the Interaction Adaptation Theory. The adaptation patterns used by Deaf students in higher education are interactional synchronization, reciprocal, and compensation. Based on this research, it can be concluded that Deaf students adapt by making language adjustments, using verbal symbols, and supported by writing.